NARROWING THE DIGITAL DIVIDE OF PEOPLE WITH DISABILITIES TO ENSURE THE TECHNOLOGY AND SOCIAL INCLUSION - Wahab, Riva'atul Adaniah (Kementerian Komunikasi dan Informatika R.I., 2019)
The digital divide for disabilities is a barrier to information acquisition, which is a basic need for self-development, social environment, and participation in national development. However, the implementation of Indonesian government policies and programs still has not shown the expected results. From the access aspect, some disabilities cannot obtain ICT infrastructures. Moreover, the challenge in accessing the government web is due to the inconsistent implementation of policies. From the ability aspect, the stigma of discrimination that is still developing in educational institutions and the private sector are an integral obstacle to encourage productivity, absorption in the workforce, or open employment opportunities. Thus, the target of fulfilling the proportion of people with disabilities in employment cannot be achieved. Those require collaboration and cooperation between the central government sector, local and central government, central government and private, and educational institutions to fulfill their rights and be able to compete in local, national, and international scale. Furthermore, a joint commitment is required in the form of policy or affirmative policy accompanied by supervision and periodic evaluation with clear standards that encourage the fulfillment of the rights of people with disabilities to ICT.Â